The Buddhist unconscious : the ālaya-vijñāna in the context of Indian Buddhist thought - Waldron, William S., 1954- (RoutledgeCurzon critical studies in Buddhism., 2004)
This study focuses on the development of the concept of unconscious mind within Indian Buddhist thought, presents issues of conception of mind and examines the doctrinal and philosophical arguments described and defended it.